Elevated Interleukin-18 Receptor Accessory Protein Mediates Enhancement in Reactive Oxygen Species Production in Neutrophils of Systemic Lupus Erythematosus Patients - Ma, Jie (Cells, 2021)
Interleukin-18 receptor accessory protein (IL18RAP) is an indispensable subunit for the IL-18 receptor (IL-18R) complex’s ability to mediate high-affinity IL-18 binding and signalling transduction. Interest in IL-18 in systemic lupus erythematosus (SLE) has been mostly focused on its role as a type 1 T helper cell-driving cytokine. The functional significance of IL18RAP in mediating the IL-18-driven response in myeloid cells in SLE remains largely unexplored. This study aimed to investigate the expression and function significance of IL18RAP in neutrophils of SLE patients. By qRT-PCR and Western blot analyses, elevated expressions of IL18RAP mRNA and protein were observed in neutrophils from SLE patients—particularly those with a history of nephritis. IL18RAP expression correlated negatively with complement 3 level and positively with disease activity, with higher expression in patients exhibiting renal and immunological manifestations. The increased IL18RAP expression in SLE neutrophils could be attributed to elevated type I interferon level in sera. Functionally, neutrophils from SLE patients showed higher IL-18-mediated enhancement in reactive oxygen species (ROS) generation, which showed positive correlation with IL18RAP expression and could be neutralized by anti-IL18RAP blocking antibodies. Taken together, our findings suggest that IL-18 could contribute to SLE pathogenesis through mediation of neutrophil dysfunction via the upregulation of IL18RAP expression.